Prawno-finansowe formy powiązań przedsiębiorstw państwowego przemysłu terenowego - Dębowska-Romanowska, Teresa; Kosikowski, Cezary (Wydział Prawa i Administracji UAM, 1969)
The subject of the consideration of the authors are the settling of the enterprises of the regional industry with the state budget and the range of action connected with it from the side of National Council. These considerations are based on the examination of income and expenses of the regional budget of the voivodeship of Łódź. The authors are interested mainly in the first stage of settling of the enterprise with the budget that covers the turnover tax or the objective estimates and positive or negative balance of the budget. These settlings form the profit of the enterprises. In the phase of the division of profit there follow farther settlings of the budget: the payments of the profit to the budget or estimates for the covering of the losses of the enterprises. In addition to that the authors are dealing with the maturity of collections of the social insurance and tax from immovables and on the other hand the financing of supplies and investments of the regional enterprises considering of the mutual relation of financing the budget to the credit bank and to the division of the amortizational transcript of the enterprises. The conclusions driven out of these considerations concern the tendency to the differentiation of the enterprises with the budget and the share of the profit of the budget out of the regional industry in the complex of income of the budget of the voivodeship.
Legal and Financial Forms of Connections of the Business on the Regional Industry